What Are the “Costs and Benefits” of Meat-Eating in Human Evolution? The Challenging Contribution of Behavioral Ecology to Archeology - Daujeard, Camille; Prat, Sandrine (Frontiers in Ecology and Evolution, 2022)
Despite the omnivorous diet of most human populations, meat foraging gradually increased during the Palaeolithic, in parallel with the development of hunting capacities. There is evidence of regular meat consumption by extinct hominins from 2 Ma onwards, with the first occurrence prior to 3 Ma in Eastern Africa. The number of sites with cut-marked animal remains and stone tools increased after 2 Ma. In addition, toolkits became increasingly complex and various, facilitating carcass defleshing and marrow recovery, and the removal of quarters of meat to avoid carnivore competition. After 1.8 Ma, the cooperative (i.e., social) hunting of large herbivores emerged. How can we assess the energy costs and benefits of meat and fat acquisition and consumption for hunter-gatherers in the past, and is it possible to accurately evaluate them? Answering this question would provide a better understanding of extinct hominin land use, food resource management, foraging strategies and cognitive abilities related to meat acquisition, processing and consumption. According to the Optimal Foraging Theory (OFT), resources may be chosen primarily on the basis of their efficiency rank in term of calories. But, could other factors, and not only calorific return, prevail in the choice of prey, such as the acquisition of non-food products, like pelts, bone tools or ornaments, or symbolic or traditional uses? Our main goal here is to question the direct application of behavioural ecology data to archaeology. For this purpose, we focus on the issue of meat and animal fat consumption in human evolution. We propose a short review of available data from energetics and ethnographic records, and provide examples of several various-sized extant animals, such as elephants, reindeer or lagomorphs, which were some of the most common preys of Palaeolithic hominins.